Perceptual Information or Informed Perception? Synesthesia and Sound-Art (International Journal on Stereo & Immersive Media, 2017)
PERCEPTUAL INFORMATION OR INFORMED PERCEPTION? SYNESTHESIA AND SOUND-ART   RONIT GHOSH -  St Stephen’s College, Delhi, India